IMPLEMENTASI PENDIDIKAN KARAKTER DI SDIT MISBAHUL HUDA PAMANUKAN - Hasyim, Adam; Darmiyanti, Astuti; Ferianto, Ferianto (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2023)
Character education is one of the important aspects as a form of mindset that supports various competencies needed to support the future of the younger generation. The purpose of this study is to examine the implementation of character education at SDIT Misbahul Huda Pamanukan. The method used in this study is qualitative research with a descriptive approach. Data collection uses documentation, interviews and observation techniques conducted at SDIT Misbahul Huda Pamanukan with 10 educators and 57 students. The results of this study provide information about the implementation of character education at SDIT Misbahul Huda Pamanukan which can be realized by combining programs in learning and self-development activities implemented learning character values. The activities in the merger program are composed of routine activities, hospitality, and school activity arrangements. Theobstacles to the implementation of character education at SDIT Misbahul Huda are the presence of students with spoiled attitudes towards educators and other students, the influence of the external environment and friends, and the presence of some students who have a lack of understanding which still takes time. The conclusion that can be drawn from this study is that the implementation of character education at SDIT Misbahul Huda Pamanukan is good and it is necessary to find solutions to immediately overcome the obstacles in the field. Keywords: character education, primary school, younger generation